Analisa Kinerja Koil Aftermarket Terhadap Performa Kerja Mesin Pada Scooter Vespa PX 150 - Jagad Baroansyah; Rizal Hanifi; Aa Santosa (Peneliti.net, 2023)
Over time, the performance of a motorcycle decreases due to our age or behavior when driving a vehicle. Therefore, there is a need for a solution to restore or even improve the performance of the motorcycle without having to replace the engine. One way to improve the combustion process is to improve the ignition system to improve engine performance. The components of the ignition system that affect the combustion process include CDI, coils, spark plug cables, spark plug caps, and spark plugs. Changes in ignition system components need to be made to see the difference in power produced and how much impact and effect it will have if using aftermarket coil products. From the results of the analysis and tests that have been carried out by the author on the vespa px 150 scooter by comparing between the standard coil and the aftermarket coil regarding power, torque, and rpm obtained results, when using the aftermarket coil, it was found that the results of increasing torque in the 3rd gear speed up with a value of 12.99 and getting the results of increasing power and torque at the acceleration of gear 4 with values of 10.28 and 13.52 And KOil Aftermaret does not fully increase the power and torque on the Vespa PX 150 sccoter, because there is only an increase in power and torque at acceleration 3 and 4 which indicates the condition of the engine is already at greater revs.